Helicobacter Pylori Infection in Canadian and Related Arctic Aboriginal Populations - Karen J Goodman; Kevan Jacobson; Sander Veldhuyzen van Zanten (Canadian Journal of Gastroenterology)
In 2006, the Canadian Helicobacter Study Group identified Aboriginal communities among Canadian population groups most at risk of Helicobacter pylori-associated disease. The objective of this systematic review was to summarize what is known about the H pylori-associated disease burden in Canadian and related Arctic Aboriginal populations to identify gaps in knowledge. Six health literature databases were systematically searched to identify reports on H pylori prevalence in Canadian population groups, or any topic related to H pylori in Canadian Aboriginals, Alaska Natives or Aboriginals of other Arctic regions. Identified reports were organized by subtopic and summarized in narrative form. Key data from studies of H pylori prevalence in defined populations were summarized in tabular form. A few Arctic Aboriginal communities were represented in the literature: two Canadian Inuit; one Canadian First Nation; two Greenland Inuit; one Russian Chutkotka Native; and several Alaska Native studies. These studies uniformly showed elevated H pylori prevalence; a few studies also showed elevated occurrence of H pylori-related diseases and high rates of treatment failure. Based on the evidence, it would be warranted for clinicians to relax the criteria for investigating H pylori and related diseases in patients from Arctic Aboriginal communities, and to pursue post-therapy confirmation of eradication. Additional community-based research is needed to develop public health policies for reducing H pylori-associated health risks in such communities.